ЗАСТОСУВАННЯ МЕТОДУ ЦИФРОВОЇ ФІЛЬТРАЦІЇ ПІД ЧАС КОРЕКЦІЇ ФОРМИ СТРУМУ В МЕРЕЖАХ З АЛЬТЕРНАТИВНИМИ ДЖЕРЕЛАМИ ЖИВЛЕННЯ - Подейко, П.П.; Губаревич, В.М.; Гребенюк, В.Г. (Інститут електродинаміки НАН України, Київ, 2026)
It is proposed to use a digital notch filter to form a reference compensation signal for a parallel single-phase active current harmonic filter, which is simple and flexible compared to known methods in its technical implementation. Mathematical modelling of the digital filter was performed in Matlab, and the results of the practical implementation of the filter-compensating device are presented, confirming the main theoretical results of the study. References 8, figures 6.